Bio-inspired mechanisms for artificial self-organized systems - Mano, Jean-Pierre (Informatica (Ljubljana), 2006)
Self-organization is a growing interdisciplinary field of research about a phenomenon that can be observed in the Universe, in Nature and in social contexts. Research on self-organization tries to describe and explain forms, comlex patterns and behaviours that arise from a collection of entities without an external organizer. As researchers in artificial systems, our aim is not to mimic self-organizing phenomena arising in Nature, but to understandand to control underlying mechanisms allowing desired emergence of forms, complex patterns and behaviours. Rather that attempting to eliminate such self-organization in artificial systems, we think that this might be deliberately harnessed in order to reach desiderable global properties. In this paper we analyze three forms of self-organization: stigmergy, reinforcement mechanisms and cooperation. The amplification phenomena founded in stigmergic process or in reinforcement process are different forms of positive feedbacks that play a major role in building group activity or social organization. Cooperation is a functional form for self-organization because of its ability to guide behaviours in order to obtain a relevant collective one. For each forms of self-organisation, we present a case study to show how we trasposed it to some artificial systems and then analyse the strengths and weakness of such an approach.
Keywords: informatika; information science; biološki sistemi; samoorganizacija